Perlindungan Hukum terhadap Pencipta Karya Sinematografi dalam Pembajakan Film pada Situs Streaming Ilegal : Ditinjau dari Undang-Undang Informasi dan Transaksi Elektronik - Maria Oktaviani Kartika Tua; Aksi Sinurat; Adrianus Djara Dima (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2024)
Internet users in the use of information have given rise to two opposite sides, where on the one hand it is easier in terms of access and utilization of information, while on the other hand it causes various kinds of illegal acts, one of which is copyright infringement in the form of film piracy which is currently inserted through illegal streaming sites resulting in losses for the creators of cinematographic works. This of course violates the ITE Law and the Joint Regulation of the Minister of Law and Human Rights and the Minister of Communication and Informatics concerning the Implementation of Content Closure and/or User Access Rights, Copyright Infringement and/or Related Rights in Electronic Systems. This research is a normative juridical research using a legislative and conceptual approach, using legal materials from literature and the internet as a source of legal materials. The results of the study show: (1) The form of legal protection for the creators of cinematographic works in film piracy on illegal streaming sites is reviewed from the ITE Law in a preventive manner regulated in Articles 23-25, Article 25, Article 32 paragraphs (1) and (2) of the ITE Law and has been repressively regulated in Article 48 paragraphs (1) and (2) of the ITE Law and the Joint Regulation of the Minister of Law and Human Rights & the Minister of Communication and Information related to Content Closure. (2) The effectiveness of the legal protection provided by the government to the creators of cinematographic works in the piracy of films on illegal streaming sites provided by the government through the ITE Law and the Joint Regulation of the Minister of Law and Human Rights and the Minister of Communication and Informatics related to site blocking cannot be said to be effective until now because the legal factor itself has not sufficiently accommodated the protection of creators clearly in the event of film piracy on illegal streaming sites.